Effect of 0.5 at.% indium on thermoelectric properties of gallium doped-zinc oxide bulk - Pham, Anh Tuan Thanh; Trinh, Ly Thi; Pham, Ngoc Kim; Nguyen, Truong Hung; Hoang, Dung Van; Lai, Hoa Thi; Ta, Hanh Kieu Thi; Le, Thu Bao Nguyen; Le, Ngoc Van; Tran, Vinh Cao; et al. (Vietnam Journal of Science and Technology, 2020)
Thermoelectrics (TE) is well-known as a non-smoke technology for electricity production from waste heat and for greenhouse effect reduction. Enhancing power factor (PF = S2sigma, where S is Seebeck coefficient and sigma is electrical conductivity) and figure of merit of TE materials to achieve high-performance TE devices has attracted much scientific attention. Doping foreign elements into host bulk structure is a basic and traditional solution to modify the thermoelectric properties of materials. In this work, we use small amount of 0.5 at.% In as dopant which is incorporated into Ga-doped ZnO (GZO) bulk by using solid-state reaction method. The effects of In addition on electrical and thermoelectric characterizations of Ga-doped ZnO bulk are discussed in detail. As a result, the electrical conductivity of the IGZO bulk increases more than 20% as compared to the GZO bulk. The Seebeck coefficient decreases insignificantly, which leads to enhancing power factor by 55% from 184.4 uW/mK2 (GZO) to 285.2 uW/mK2 (IGZO) at 500oC. The results open possibility to enhance the figure of merit of pure and doped ZnO material.